2016
DOI: 10.5312/wjo.v7.i12.776
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and treatment of internal impingement of the shoulder in overhead athletes

Abstract: One of the most common pathologic processes seen in overhead throwing athletes is posterior shoulder pain resulting from internal impingement. “Internal impingement” is a term used to describe a constellation of symptoms which result from the greater tuberosity of the humerus and the articular surface of the rotator cuff abutting the posterosuperior glenoid when the shoulder is in an abducted and externally rotated position. The pathophysiology in symptomatic internal impingement is multifactorial, involving p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 55 publications
0
21
0
4
Order By: Relevance
“…In athletes with pathologic GIRD, shoulder stiffness, the need for a prolonged warm-up, and loss of velocity (dead arm) are often the initial complaints. 25 Pain is often aspecific, localizing to the posterior shoulder, and the late cocking position is often provocative. 26 Palpation of the posterior joint line and surrounding soft tissue can reproduce pain.…”
Section: Diagnosismentioning
confidence: 99%
“…In athletes with pathologic GIRD, shoulder stiffness, the need for a prolonged warm-up, and loss of velocity (dead arm) are often the initial complaints. 25 Pain is often aspecific, localizing to the posterior shoulder, and the late cocking position is often provocative. 26 Palpation of the posterior joint line and surrounding soft tissue can reproduce pain.…”
Section: Diagnosismentioning
confidence: 99%
“…In overhead athletes (e.g., baseball pitchers), the shoulder joint is predisposed to incur altered configurations of the GH joint, ROM deficits, and muscle weakness, resulting in an SD whose grade of injury increases with the level of the competition [151][152][153][154][155][156]. In elite athletes with common internal impingement, researchers have found that treatments focused on intense non-operative approaches provide better outcomes than other treatments and that physical training protocols might be integrated into their usual daily exercises [157][158][159]. Physical training protocol should promote the reinforcement of the scapular muscles and guarantee the optimal length-tension relationship of RC muscles [160].…”
Section: Treatmentmentioning
confidence: 99%
“…A ''kissing lesion'' can be seen along the labrum in overhead athletes with internal impingement and partial articularsided rotator cuff tears. 11 Seventeen patients with internal impingement demonstrated a 71% incidence of posterosuperior labral lesions. 32 Additionally, in 41 overhead athletes with internal impingement, posterosuperior labral damage was seen in 88% during arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The American Journal of Sports Medicine 2020;48 (11):2747-2754 DOI: 10.1177/0363546520944147 Ó 2020 The Author(s) 5-in-5 lengthening (IFL) is a safe, effective, and minimally invasive technique to treat PIS. 7,13,14,16,23,29,30 Soft tissuesparing IFL performed at the level of the joint, in which only the tendinous portion of the iliopsoas is cut, allows the iliopsoas to elongate and may help preserve its muscle path, flexion strength, and hip stability.…”
mentioning
confidence: 99%